Analysis of garlics lateral conveying performance based on EDEM. (August 2020) - Huang, Weitao; Zhao, Dong; Liu, Cheng; Meng, Xianjiang; Du, Wenhao
Abstract: This article studied the effect of different conveyor belt speeds on garlics transportation in the process of garlics harvesting and lateral conveying. The lateral conveying process of garlics is simulated by EDEM, and the optimal transportation speed interval is obtained by simulating different transportation speeds. The simulation results show that the conveying speed range of conveyor belt is 2.46-3.46 m /s when the plant spacing of garlics is 0.1 m, the row spacing is 0.12 m, and the 16 harvesting units of garlics combine harvester harvest at the speed of 2 m/s at the same time, which can effectively avoid the problem of garlics accumulation on the lateral conveyor belt when the conveying speed is too slow, and garlics leakage and garlics secondary damage problems when the delivery speed is too fast. The research can provide some theoretical reference for the design of garlics transversal conveyer and the selection of conveying speed.